2015
DOI: 10.1007/s10571-015-0233-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of RAGE in Alzheimer’s Disease

Abstract: Receptor for advanced glycation end products (RAGE) is a receptor of the immunoglobulin super family that plays various important roles under physiological and pathological conditions. Compelling evidence suggests that RAGE acts as both an inflammatory intermediary and a critical inducer of oxidative stress, underlying RAGE-induced Alzheimer-like pathophysiological changes that drive the process of Alzheimer's disease (AD). A critical role of RAGE in AD includes beta-amyloid (Aβ) production and accumulation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
151
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(156 citation statements)
references
References 139 publications
1
151
0
Order By: Relevance
“…Advanced glycation end products and its soluble receptor have been implicated in the pathogenesis of AD [52,53]. Although not statistically significant, levels of the soluble form of RAGE (sRAGE) were decreased 48% in African Americans and indicated a medium effect size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced glycation end products and its soluble receptor have been implicated in the pathogenesis of AD [52,53]. Although not statistically significant, levels of the soluble form of RAGE (sRAGE) were decreased 48% in African Americans and indicated a medium effect size.…”
Section: Discussionmentioning
confidence: 99%
“…Although not statistically significant, levels of the soluble form of RAGE (sRAGE) were decreased 48% in African Americans and indicated a medium effect size. sRAGE lacks the transmembrane domain and intracellular tail and is thought to act as an extracellular decoy by sequestering RAGE ligands [47,[53][54][55]. That sequestration can then prevent the activation of RAGE and its downstream pathological signaling effects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that interaction between AGEs and RAGE activates the generation of oxidative stress and production of proinflammatory cytokines in various types of cells that have been implicated in metabolic and many other disease statuses [1316]. Furthermore, Monden et al have shown that RAGE affects adipocyte hypertrophy and insulin sensitivity in mice [17].…”
Section: Introductionmentioning
confidence: 95%
“…This is possible because of the presence of proinflammatory receptors on their surface. Microglia is able to identify and bind Aβ oligomers and fibrils and the amyloid precursor protein (APP)57 through a large number of receptors, including scavenger receptor class A type 1, MARCO, scavenger receptor class B member 1, CD36, and the receptor for advanced glycation end product,58,59 G protein-coupled receptors formyl peptide receptor 2 60 and chemokine-like receptor 1,61 toll-like receptors (TLRs) TLR2,62 TLR4, and the CD14 coreceptor, and α6β1 integrin 63. The outcome of the bond between Aβ and these receptors is the production of inflammatory mediators such as cytokines (interleukin [IL]-1α, IL-1β, IL-6, IL-8, IL-12, IL-18, and IL-23, interferon (IFN)-γ, tumor necrosis factor [TNF]-α, and granulocyte-macrophage colony-stimulating factor [GM-CSF]),64,65 chemokines (monocyte chemotactic protein 1 (MCP1), MCP-113, fractalkine),66,67 chemoattractant proteins, prostaglandins, complement factors, thromboxanes, pentraxins, NO, reactive oxygen species, leukotrienes, proteases, protease inhibitors, adhesion molecules (interaction between CD40-CD40 ligand CD40L),68 coagulation factors, and C-reactive protein, most of which are detectable in AD animal and/or in the brain or cerebrospinal fluid of AD patients 25,69,70.…”
Section: The Pathophysiology Of Neuroinflammation and Its Role In Alzmentioning
confidence: 99%